Genome assembly and annotation of the Sharp-nosed Pit Viper Deinagkistrodon acutus based on next-generation sequencing data - Xinyu Wang; Lirong Liu; Wenbiao Zhu; Shiqing Wang; Minhui Shi; Shuhui Yang; Haorong Lu; Jun Cao (GigaByte)
The study of the currently known >3,000 species of snakes can provide valuable insights into the evolution of their genomes. Deinagkistrodon acutus, also known as Sharp-nosed Pit Viper, one hundred-pacer viper or five-pacer viper, is a venomous snake with significant economic, medicinal and scientific importance. Widely distributed in southeastern China and South-East Asia, D. acutus has been primarily studied for its venom. Here, we employed next-generation sequencing to assemble and annotate a highly continuous genome of D. acutus. The genome size is 1.46 Gb; its scaffold N50 length is 6.21 Mb, the repeat content is 42.81%, and 24,402 functional genes were annotated. This study helps to further understand and utilize D. acutus and its venom at the genetic level.